Exploring the most visible websites on cutaneous T‐cell lymphoma—revealing limited quality of patient health information on the internet. (26th July 2022) - Özistanbullu, D.; Weber, R.; Kleemann, J.; Jäger, M.; Kippenberger, S.; Kaufmann, R.; Meissner, M.
Abstract: Background: Patients diagnosed with cancer frequently search the Internet for health information. Yet, the quality of CTCL online information has not been investigated so far. Objectives: The aim of this study was to identify and assess the most visible websites on CTCL. Methods: An Internet search on the top three search engines Google, Yahoo and Bing was performed for the terms 'cutaneous T‐cell‐lymphoma', 'mycosis fungoides' and 'Sézary syndrome'. After selecting the most frequented websites suitable for patients' information, we investigated content quality, readability and popularity. Eighty‐nine websites were evaluated for HONcode quality certification, social media popularity, Alexa popularity rank, topicality and readability levels. Furthermore, the websites' content on 13 major topics according to guidelines on CTCL was assessed. Results: Twenty‐three (25.8%) websites were HONcode certified. Evaluated websites were difficult to read requiring at least 9 years of US school education to properly understand the information. More than half of all websites (57.3%) have not been updated for three or more years (or did not contain any update information). We found greatly varying quality and popularity of online patient information. Out of 1157 topics (equivalent to 13 different topics on 89 websites), 59.44% were mentioned on the websites. Of these, 40% contained incorrect or incomplete information. Publicly provided websites presented the different topics more thoroughly. We could further show that HONcode certified websites received better quality and readability scores. Conclusions: We found major shortcomings regarding readability, completeness and reliability of websites on CTCL. Nevertheless, highly selected websites on CTCL can serve as a valuable and reliable source of patient information. As a consequence, oncologists have an obligation to be aware of and guide their patients to available websites that contain reliable and appropriate information.